Changes in soil properties due to intercropping: A case study - Jayasree K R; Jessy M D; Nair A N S; Punnoose K I (Rubber Board Bulletin, 2006)
A survey was conducted in the rubber holdings coming under the operational area of the Rubber Board Regional Office, Kottayam during 1999-2000 to study the changes in physico-chemical properties of the soil due to intercropping. Organic carbon content in all the selected fields was in the medium to high range and no appreciable difference was found in the fields with intercrops. Available phosphorus showed wide variation from field to field and was higher near the intercrop irrespective of the crop, compared to near rubber or in uncultivated area. Available potassium content was in the medium range in almost all the situations. Bulk density was less near intercrops compared to near rubber possibly due to the tillage operations carried out for intercrops.
Keywords: Intercropping; Soil properties